2016
DOI: 10.1038/srep34691
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cells induce Notch-mediated hepatocyte conversion in a common mouse model of intrahepatic cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (ICC) is a malignant epithelial neoplasm composed of cells resembling cholangiocytes that line the intrahepatic bile ducts in portal areas of the hepatic lobule. Although ICC has been defined as a tumor arising from cholangiocyte transformation, recent evidence from genetic lineage-tracing experiments has indicated that hepatocytes can be a cellular origin of ICC by directly changing their fate to that of biliary lineage cells. Notch signaling has been identified as an essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…Malato Y. et al found newly formed hepatocytes derived from preexisting hepatocytes in the normal liver and acute injury; further, conversion of hepatocytes into BECs was not found in commonly used models of biliary injury 10 . Previous studies and our study demonstrated that hepatocytes undergo reversible ductal metaplasia in response to chronic injury 39,40 , expand and subsequently redifferentiate into functional hepatocytes 17 . The difference between Malato Y.…”
Section: Discussionsupporting
confidence: 68%
“…Malato Y. et al found newly formed hepatocytes derived from preexisting hepatocytes in the normal liver and acute injury; further, conversion of hepatocytes into BECs was not found in commonly used models of biliary injury 10 . Previous studies and our study demonstrated that hepatocytes undergo reversible ductal metaplasia in response to chronic injury 39,40 , expand and subsequently redifferentiate into functional hepatocytes 17 . The difference between Malato Y.…”
Section: Discussionsupporting
confidence: 68%
“…Meanwhile, the limitation of use of an Mx‐Cre recombination that induces Jagged1 deletion in a non‐cell type‐specific manner has to be carefully considered. A recent study has implicated Jagged1 expression in macrophages,39 and the lack of Jagged1 expression in many types of cells, including immune cells, may have influenced the results obtained in the present study. Work is in progress in our laboratory to establish a myofibroblast‐specific model of Jagged1 deletion.…”
Section: Discussionmentioning
confidence: 75%
“…In a mouse model of thioacetamide (TAA)-induced intrahepatic cholangiocarcinoma, KCs accumulate around the central vein area and express Notch ligand Jagged-1 rapidly after the initiation of the TAA treatment, coinciding with the activation of Notch signaling in pericentral hepatocytes. Depletion of KCs prevents the Notch-mediated hepatocytes transformation to cholangiocytes, suggesting that KCs contribute to the cell fate change in hepatocytes (109). Another study has also demonstrated that KCs are required for the proliferation of liver progenitor cells that can differentiate into hepatocytes in a model of cholinedeficient, ethionine-supplemented diet-mediated liver injury and regeneration (110).…”
Section: Crosstalk Between Hepatic Macrophages and Hepatocytesmentioning
confidence: 99%